A viscount for the Egyptian Princess - Helmy, Heba (Harlequin, 2024)
An unforgettable meeting in Paris. An unexpected reunion in Egypt. Viscount Louis Wesley is captivated by the beautiful woman he meets at the Louvre. He never expects to see her again, but then he arrives in Egypt for his royal best friend’s wedding and discovers she’s the bride, Princess Mervat! Learning it’s a convenient match that both intend to avoid, Louis vows to help. The stakes may be high, but Louis’s biggest challenge will be resisting falling for the princess himself!